Improving Elementary School Teacher Candidates’ Views of Nature of Science Through Intensive Education - Tugba Ecevit; Yalcin Yalaki; Sevgi Kingir (Journal of Education in Science, Environment and Health, 2018)
Elementary school teacher candidates’ (student teachers or STs) views of nature of science are important for an effective science teaching that aims to improve children’s scientific literacy. The purpose of this study was to improve STs’ views of nature of science through an intensive intervention. The study group consisted of 65 third year STs who were attending a major university in Ankara Turkey during the 2015 – 2016 fall semester. An educational program with a variety of activities that were designed to help improve participants’ views of nature of science was applied and the effect of this program was evaluated. The educational program included historical approach activities, generic activities, explicit-reflective approach activities, and media news analysis activities which were applied in three hour periods over the course of nine weeks. Both qualitative and quantitative data were collected in this convergent parallel mixed method study. At the beginning of the study, the participating STs had naive views of nature of science and some misconceptions. After the applied educational program, STs’ views of nature of science improved and they adopted more contemporary views of science. As a result, a long-term intervention with multiple methods of teaching with different kinds of activities was found to be an effective approach for improving STs’ understanding of nature of science.